Eficaia del tratamiento fidioterapeutico en pacientes con gonartrosis que acuden al departamento de fisiatría atendidios enel Hospital del seguro de Riobamba, durante el período de agosto 2010 a enero 2011 - Pinduisaca Pinduisaca, Adriana del Rocio (2011)
Knee osteoarthritis, wear-and-tear arthritis or degenerative joint disease, is a process of cartilageaging, joint surface and the degeneration of the menisci, the bone beneath the cartilage changes to receive more pressure causing pain and thickening of the joint sheaths, the joint becomes irritated and produces large amounts of fluid causing joint effusion. This research is structured systematically to be understood by its beneficiaries as follows: Chapter I: Problem Statement, Problem Formulation, General Objective, Specific Objectives, and Justification. Chapter II: The Theoretical Framework with bibliographic arguments concerning to the subject, Definition of Basic Terms, Hypotheses, Variables. Chapter III: Methodological Framework, Population and Sample, Data CollectionTechniques and Tools, Techniques for the Analysis and Interpretation of Data, Information Processing, Hypotheses Testing. Chapter IV: Conclusions, Recommendations.